PENINGKATAN KOMPETENSI PTK PNF MELALUI KAJI TINDAK TERINTEGRASI BERBASIS KOMPETENSI (Integrated Competency-based Action Research) - Tantra, Dewa Komang (JIV-Jurnal Ilmiah Visi, 2006)
The article points out global phenomena that should be considered in developing professionalism of NFE educators. The phenomena are (1) globalization, (2) universalization of education, (3) competency-based education, (4) constructivism, (5) ICT-based education, (6) regional autonomy, (7) National Education Systems Act, (8) Government Regulation on National Standard Education, (9) national competitiveness, (10) education autonomy, (11) Organizational health. Other aspects influencing NFE programs are philosophy and trends in education regarding (1) competency, and life skill-based education, (2) participant-oriented instruction, (3) the use of media for learning especially electronic media, and (4) basic technology education. NFE deals with problems in regards of educators, that is the small number and unqualified personnel. Topic suggests that a model called Integrated competency-based action research would help improve the quality of educators’ performance. The model is systemic, interdependent, and functional. It recommends that partnerships with all respective parties are prime of important.